Pengaruh Mekanisme Online terhadap Tingkat Kepercayaan yang Mempengaruhi Intensi Pembelian Kembali - Della Liudi; Hee Nanda Dlaneri; I Putu Aditya Wardana; Marcha Ramada; Stefani Pardi (Indonesian Business Review, 2019)
Online shopping becomes apart of lifestylefor Indonesian. It leads to the business in this sector is prospective . The purpose of this paper is to find out how seller, institution, and experience-based online trust-building mechanisms affect customers trusts in e-marketplace and e-se//er of emarketp/ace, which shape the repurchase intentions. According to research finding using 380 respondent s, the perceived usefulness of seller and institutional-based mechanisms affect trust in e-marketplace. Meanwhile, the seller and experience-based mechanism influence the trust in e-seller of e-marketplace. Thus, both of the trusts influence repurchase intentions.